1992
DOI: 10.1016/0378-1097(92)90408-g
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of the gene encoding type F neurotoxin of Clostridium botulinum

Abstract: Primers designed to conserved regions of botulinum and tetanus clostridial toxins were used to amplify DNA fragments from non-proteolytic Clostridium botulinum type F (202F) DNA using polymerase chain reaction technology. The fragments were cloned and the complete nucleotide sequence of the gene encoding type F toxin determined. Analysis of the nucleotide sequence demonstrated the presence of an open frame encoding a protein of 1274 amino acids, similar to other botulinum neurotoxins. Upstream of the toxin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 7 publications
(13 reference statements)
0
25
0
1
Order By: Relevance
“…The heavy chain of C. baratii toxin F shows higher sequence similarity, 73.6 and 68.4%, with the heavy chains of C. botulinum toxins F and E, respectively (5). Since the heavy chains apparently determine the receptor function, the noted similar homologies between the heavy chains of F and E indicate a shared receptor.…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 95%
See 1 more Smart Citation
“…The heavy chain of C. baratii toxin F shows higher sequence similarity, 73.6 and 68.4%, with the heavy chains of C. botulinum toxins F and E, respectively (5). Since the heavy chains apparently determine the receptor function, the noted similar homologies between the heavy chains of F and E indicate a shared receptor.…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 95%
“…Recently, there have been several studies on the genetic and structural relationships among clostridial neurotoxins (5,8,9,13). Sequence analysis has shown that there is high genetic homology between the toxins E produced by C. butyricum and C. botulinum but low relatedness between the genes coding for the toxins F of C. baratii and saccharolytic C. botulinum.…”
Section: Vol 40 2002 Notes 2261mentioning
confidence: 99%
“…Based on published DNA sequences of the BoNT gene (2,8,9,27,33,34,35), four new primer pairs with each being specific for either C. botulinum type A, B, E, or F were designed ( Table 2). The primers were selected from the nonhomologous regions of the BoNT types A, B, E, and F gene by using the Primer 3 software (S. Rozen and H. J. Skaletsky, Primer 3, Whitehead Institute for Biomedical Research, Cambridge, Mass.…”
Section: Methodsmentioning
confidence: 99%
“…The abovementioned experimental hurdle was circumvented by devising an innovative technique for making BoNTs recombinantly in Escherichia coli after the genes for several BoNT serotypes had been cloned [13][14][15][16][17][18][19][20][21]. Prior to this, progress had been hampered by difficulties encountered when separately expressing the chains due to improper or incomplete folding, insolubility, and further problems after their reconstitution, particularly recovering the biological activities [22].…”
Section: Strategy For Successfully Generating Recombinant Bonts As Scmentioning
confidence: 99%